Reliability and redundancy allocation analysis applied to a nuclear protection system (Brazilian Journal of Radiation Sciences (BJRS), 2021)
Brazil is constructing with national technology two small nuclear reactors for propulsion and for radioisotope production with thermal power levels between 20 and 50 MW. These nuclear reactors fit more in the class of small modular reactors (SMR) than in the class of large nuclear power plants. In this article we apply the design approach of SMRs to propose an architecture of reactor protection systems for the small reactor under construction in the country. To do that the probabilistic analysis of the architecture of a nuclear reactor protection system is evaluated to determine the sensitivity of the components through an Reliability Block Diagram modeling. It was evaluated the modification of the architecture and the addition of redundancies when using components with lower life time than the components usually used for this purpose. The results showed that after one year of operation, the reference RPS system presents a failure probability of 0.17 %. The modified system, with components with lower life time, presents a point reliability value only 0.070 % lower than the reference one, but this difference grows exponentially over time, and in 10 years of operation it can reach values above 95%. Using equipment with lower life time characteristics implies a greater number of redundancies and, additionally, a greater number of maintenance procedures and spare parts. Therefore, this technical feasibility analysis should consider a RAM simulation as well.